Reproductive outcomes of neonatal exposure to betamethasone in male and female rats - Figueiredo, Thamiris Moreira [UNESP]; de Barros, Jorge Willian Franco [UNESP]; dos Santos Borges, Cibele [UNESP]; Pacheco, Tainá Louise [UNESP]; de Lima Rosa, Josiane [UNESP]; Anselmo-Franci, Janete Aparecida; Kempinas, Wilma De Grava [UNESP] (Wiley, 2023)
Betamethasone (BM) is the drug of choice for antenatal corticosteroid therapy for women at risk of preterm delivery because it induces fetal lung maturation and enhances survival after birth. However, our group reported evidence of fetal programming and impaired reproductive development and function in rats exposed during the critical window of genital system development. Therefore, we aimed to investigate the effects of BM on the sexual development of rats in the period that corresponds to antenatal corticosteroid therapy in humans. Male and female rats were exposed subcutaneously to BM at 0.1 μg/g of pups' body weight or to a NaCl 0.9% solution (control) on postnatal days 1–3. It was observed that neonatal exposure to BM decreased body weight and weight gain in male and female rats during treatment. The estrous cycle was deregulated and LH level was decreased in female rats. In male rats, the sperm concentration in the caput–corpus of the epididymis was decreased, whereas the sperm transit time and sperm concentration in the cauda of the epididymis were increased. Our results demonstrated that neonatal exposure to BM impaired body growth of male and female rats, deregulated the estrous cycle of female rats, and altered sperm quality of male rats. Therefore, BM exposure from postnatal days 1 to 3 corroborated results previously observed after prenatal exposure to this drug. Despite the recognized importance of human antenatal corticosteroid therapy, the findings of this study should encourage further studies in order to minimize possible adverse postnatal effects.
Keywords: betamethasone; corticosteroid therapy; fetal programming; neonatal; sexual development